2013
DOI: 10.5433/1679-0359.2013v34n3p1077
|View full text |Cite
|
Sign up to set email alerts
|

Acúmulo de nutrientes no colmo de cana-de-açúcar em função de fontes e doses de manganês

Abstract: ResumoA baixa produtividade dos canaviais em algumas áreas pode estar relacionada a exigência e exportação da cultura da cana-de-açúcar. O objetivo deste estudo foi avaliar o efeito de cinco doses e três fontes de manganês aplicadas no sulco de plantio na cultura da cana-de-açúcar em cana planta e seu efeito residual em cana soca. O experimento foi conduzido no sítio Fujimoto, área administrada pela Destilaria Vale do Paraná S/A Álcool e Açúcar, no município de Suzanápolis -SP. O delineamento experimental util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
3
2
1
Order By: Relevance
“…The values obtained for the export of nutrients depend on the conditions under which the plants are maintained. In the present study for all nutrients examined, export values were higher than those reported by Benett et al (2013), when studying the same cultivar (RB 867515) using five doses and three sources of manganese as treatments. These authors found maximum exports of N, P, K, Ca, Mg and S of 99, 6.89, 86, 12.52, 12.11 and 11.9 kg ha -1 , respectively.…”
Section: Resultscontrasting
confidence: 79%
“…The values obtained for the export of nutrients depend on the conditions under which the plants are maintained. In the present study for all nutrients examined, export values were higher than those reported by Benett et al (2013), when studying the same cultivar (RB 867515) using five doses and three sources of manganese as treatments. These authors found maximum exports of N, P, K, Ca, Mg and S of 99, 6.89, 86, 12.52, 12.11 and 11.9 kg ha -1 , respectively.…”
Section: Resultscontrasting
confidence: 79%
“…Plant-cane First ratoon Second ratoon Average about 30% lower than those obtained in the present study. Benett et al (2013) in a study conducted with RB867515 cultivated in a Red Ultisol obtained yields of stalks that varied from 90 to 104 t ha -1 , considering that the stems correspond to approximately 80% of the natural matter, biomass productivity estimation was approximately 130 t ha -1 . Silva et al (2017a) evaluated the growth of the variety RB967515 in the first three harvest cycles, and verified a productivity of 72, 63 and 67 t ha -1 for plant-cane, first and second ratoon, respectively, therefore inferior to those obtained in the present study.…”
Section: Natural Biomass Productivity Of the Sugarcane Areamentioning
confidence: 99%
“…The varieties were similar in the Ca requirement, and evidenced for the production of one ton of sugarcane a requirement of 0.53, 0.51 and 0.66 kg of Ca in the plant-cane cycles, first and second regrowth, respectively. After high potassium and nitrogen, calcium has been the macronutrient most accumulated by sugarcane (Franco et al, 2007;Zambrosi et al, 2012;Benett et al, 2013), its high demand stems from its structural role in which Ca 2+ binds to acidic groups of membrane lipids (phospho and sulfulipids) and to cross-links between pectins, particularly in the lamella medium recently dividing cells; and its signaling role, in which Ca 2+ acts as a secondary messenger that initiates the plant responses to environmental stimulation. Also as a secondary messenger, Ca 2+ can bind to calmodulin, a protein found in the plant cell cytosol.…”
Section: Macronutrients Requirementmentioning
confidence: 99%
“…Various studies have shown that P the macronutrient least required by sugarcane (Benett et al, 2013;Rossato et al, 2016), although it is one of the elements that has most limited the cultivation of sugarcane in the tropics (Caione et al, 2013;Sousa et al, 2013;Simões Neto et al, 2015;Albuquerque et al, 2016). This fact is associated to the complex phosphorus dynamics in tropical soils, where there is predominance of 1:1 clays and iron and aluminum oxyhydroxides, which have high P adsorption capacity, promoting P fixation and reducing the efficiency of phosphate fertilization (Sanchez & Uehara, 1980).…”
Section: Resultsmentioning
confidence: 99%